Collaborating to Plan and Implement a Sex Education Curriculum for Individuals With Disabilities. (May 2017) - Sinclair, James; Kahn, Laurie G.; Rowe, Dawn A.; Mazzotti, Valerie L.; Hirano, Kara A.; Knowles, Christen
Sex education is not only a necessary component of public school curriculum, but it is also an important opportunity for students with and without disabilities to learn about their own development as emerging adults. Although comprehensive sex education is not federally mandated, many states and districts choose to offer some form of sex education to students. This article describes a five step collaborative process for planning to implement a sex education program to support the needs of students with disabilities.